The joy of half a cookie : using mindfulness to lose weight and end the struggle with food - Kristeller, Jean; Bowman, Alisa (Perigee, an imprint of Penguin Random House LLC, 2015)
"Anyone who's tried to lose weight through sheer will power knows how difficult, if not impossible, it can be. In this practical and paradigm-shifting book, Dr. Jean Kristeller presents a new alternative--a program for weight loss based on her successful Mindfulness-Based Eating Awareness Training Program. Instead of frustration, deprivation, backsliding, guilt, and a lack of results, The Joy of Half a Cookie provides simple, proven ways to lose weight and keep it off, using what we now know about the power of the mind."--